MMP20 Overexpression Disrupts Molar Ameloblast Polarity and Migration. (July 2018) - Shin, M.; Chavez, M.B.; Ikeda, A.; Foster, B.L.; Bartlett, J.D.
Ameloblasts responsible for enamel formation express matrix metalloproteinase 20 (MMP20), an enzyme that cleaves enamel matrix proteins, including amelogenin (AMELX) and ameloblastin (AMBN). Previously, we showed that continuously erupting incisors from transgenic mice overexpressing active MMP20 had a massive cell infiltrate present within their enamel space, leading to enamel mineralization defects. However, effects of MMP20 overexpression on mouse molars were not analyzed, although these teeth more accurately represent human odontogenesis. Therefore, MMP20-overexpressing mice ( Mmp20 +/+ Tg + ) were assessed by multiscale analyses, combining several approaches from high-resolution micro–computed tomography to enamel organ immunoblots. During the secretory stage at postnatal day 6 (P6), Mmp20 +/+ Tg + mice had a discontinuous ameloblast layer and, unlike incisors, molar P12 maturation stage ameloblasts abnormally migrated away from the enamel layer into the stratum intermedium/stellate reticulum. TOPflash assays performed in vitro demonstrated that MMP20 expression promoted β-catenin nuclear localization and that MMP20 expression promoted invasion through Matrigel-coated filters. However, for both assays, significant differences were eliminated in the presence of the β-catenin inhibitor ICG-001. This suggests that MMP20 activity promotes cell migration via the Wnt pathway. In vivo, the unique molar migration of amelogenin-expressing ameloblasts was associated with abnormal deposition of ectopic calcified nodules surrounding the adherent enamel layer. Enamel content was assessed just prior to eruption at P15. Compared to wild-type, Mmp20 +/+ Tg + molars exhibited significant reductions in enamel thickness (70%), volume (60%), and mineral density (40%), and MMP20 overexpression resulted in premature cleavage of AMBN, which likely contributed to the severe defects in enamel mineralization. In addition, Mmp20 +/+ Tg + mouse molar enamel organs had increased levels of inactive p-cofilin, a protein that regulates cell polarity. These data demonstrate that increased MMP20 activity in molars causes premature degradation of ameloblastin and inactivation of cofilin, which may contribute to pathological Wnt-mediated cell migration away from the enamel layer.